Discovery of a C-8 hydroxychromene as a potent degrader of estrogen receptor alpha with improved rat oral exposure over GDC-0927. Issue 16 (15th August 2019) - Labadie, Sharada S.; Li, Jun; Blake, Robert A.; Chang, Jae H.; Goodacre, Simon; Hartman, Steven J.; Liang, Weiling; Kiefer, James R.; Kleinheinz, Tracy; Lai, Tommy; Liao, Jiangpeng; Ortwine, Daniel F.; et al.
Graphical abstract: Abstract: Phenolic groups are responsible for the high clearance and low oral bioavailability of the estrogen receptor alpha (ERα) clinical candidate GDC-0927. An exhaustive search for a backup molecule with improved pharmacokinetic (PK) properties identified several metabolically stable analogs, although in general at the expense of the desired potency and degradation efficiency. C-8 hydroxychromene 30 is the first example of a phenol-containing chromene that not only maintained excellent potency but also exhibited 10-fold higher oral exposure in rats. The improved in vivo clearance in rat was hypothesized to be the result of C-8 hydroxy group being sterically protected from glucuronide conjugation. The excellent potency underscores the possibility of replacing the presumed indispensable phenolic group at C-6 or C-7 of the chromene core. Co-crystal structures were obtained to highlight the change in key interactions and rationalize the retained potency.